2012
DOI: 10.1371/journal.pntd.0001510
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni Venom Allergen Like Proteins Present Differential Allergic Responses in a Murine Model of Airway Inflammation

Abstract: BackgroundThe Schistosoma mansoni Venom-Allergen-Like proteins (SmVALs) are members of the SCP/TAPS (Sperm-coating protein/Tpx-1/Ag5/PR-1/Sc7) protein superfamily, which may be important in the host-pathogen interaction. Some of these molecules were suggested by us and others as potential immunomodulators and vaccine candidates, due to their functional classification, expression profile and predicted localization. From a vaccine perspective, one of the concerns is the potential allergic effect of these molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 44 publications
2
40
0
3
Order By: Relevance
“…This sample was analyzed by SDS-PAGE and stained with Schiff's reagent (Sigma) for detection of glycoproteins as per the manufacturer's recommendations. Bovine Serum Albumin (BSA) (Bio-Rad) (non-glycosylated protein) and rSmVAL4 (glycosylated protein) were used as controls for the specificity of the reaction [45]. The rSmCD59.1 and rSmCD59.2 proteins expressed in P. pastoris were glycosylated (products between 14.4 kDa and 20.1 kDa), based on their staining with Schiff's reagent and increased size in SDS-PAGE (as can be observed by the protein band shift in comparison to the rSmCD59.2 expressed in E. coli (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…This sample was analyzed by SDS-PAGE and stained with Schiff's reagent (Sigma) for detection of glycoproteins as per the manufacturer's recommendations. Bovine Serum Albumin (BSA) (Bio-Rad) (non-glycosylated protein) and rSmVAL4 (glycosylated protein) were used as controls for the specificity of the reaction [45]. The rSmCD59.1 and rSmCD59.2 proteins expressed in P. pastoris were glycosylated (products between 14.4 kDa and 20.1 kDa), based on their staining with Schiff's reagent and increased size in SDS-PAGE (as can be observed by the protein band shift in comparison to the rSmCD59.2 expressed in E. coli (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…Some of the venom allergen-like proteins in Schistosoma mansoni Sambon are suggested to be immune modulators and vaccine candidates (Chalmers et al 2008, Farias et al 2012. The venom allergen 5 gene is one of the major allergens identified in many insect venoms (King and Spangfort 2000) and is often associated with allergic responses in humans (Muller et al 2009).…”
mentioning
confidence: 99%
“…SmVALs can be divided into two groups and exhibit various gene expression patterns throughout the entire life-cycle, including genes exclusively expressed in stages involved in intermediate host invasion or definitive host invasion and ubiquitously expressed genes [32]. Because of their potential functional classification, expression patterns and localization, SmVALs have been proposed as potential drug targets and vaccine candidates, and some members have been well characterized recently [66][67][68]. For instance, Farias et al have demonstrated that SmVAL4 and SmVAL26 stimulate differential allergic responses in a murine model of airway inflammation [66]; and in a recent study, egg-derived SmVAL9 was found to carry an N-linked glycan containing a schistosome-specific difucosyl element and function as an immunogenic target during chronic murine schistosomiasis [68].…”
Section: Phylogenetic Analysis and Global Expression Profiling Of Thementioning
confidence: 99%
“…Because of their potential functional classification, expression patterns and localization, SmVALs have been proposed as potential drug targets and vaccine candidates, and some members have been well characterized recently [66][67][68]. For instance, Farias et al have demonstrated that SmVAL4 and SmVAL26 stimulate differential allergic responses in a murine model of airway inflammation [66]; and in a recent study, egg-derived SmVAL9 was found to carry an N-linked glycan containing a schistosome-specific difucosyl element and function as an immunogenic target during chronic murine schistosomiasis [68]. In our study, 20 non-redundant S. japonicum venom-allergen-like protein (SjVAL) genes were identified in the genome.…”
Section: Phylogenetic Analysis and Global Expression Profiling Of Thementioning
confidence: 99%